Kepimpinan servant dan pengaruhnya terhadap pengurusan perubahan di sekolah - Ibrahim, Izani; Don, Yahya (Fakulti Pendidikan, Universiti Kebangsaan Malaysia., 2014)
This study aimed to identify the influence of servant leadership on the change management in schools. This crosssectional survey involving 342 secondary school teachers in the northern zone (Perlis, Kedah, Penang and Perak) by using questionnaire as the research instrument.The instrument used are Servant Leadership Scale (SLS) and Change Facilitator Style Questionnaire (CFSQ).Results showed that servant leadership contributed to the change management in schools.Thus, servant leadership should be applied and practiced by school leaders to improve the success of change management, thereby improving school performance .